An overview of the cheesemaking process - Bintsis, Thomas; Papademas, Photis (My University, 2017)
This chapter aims at describing the most important parameters that one should take into consideration when embarking on the journey of transforming milk into cheese. Cow's milk, the major ingredient used in global cheesemaking, is produced by several breeds. A high-milk-producing cow breed is the Holstein-Friesian, representing 90% of total cow's milk production. The chapter discusses the basic milk components and how they affect cheesemaking. Milk quality is certainly affected by animal nutrition, and taints in milk occur when are animals are fed unsuitable types of herbage. Animal feeding strategies could lead to enrichment of milk with important fatty acids such as conjugated linoleic acid (CLA). Milk for cheesemaking may be acidified by its indigenous LAB or by using a 'backslop' culture, that is, a volume of whey retained from a previous day's cheesemaking. In such cases, the rate of acidification is unpredictable, and the growth of undesirable bacteria very often leads to defective cheeses.
Keywords: Analytical methodologies; Cheesemaking; Food authentication; Molecular markers; Protected land-related labels; Protected tradition-related labels; Traceability system